RESTRUCTURING THE CONCEPT OF SAHAM WAQF FOR CONTINUOUS LIQUID WAQF FUND IN MALAYSIA - Mohsin, Aminah; Haji Mohammad, Mohammad Tahir Sabit (Jurnal Syariah, 2023)
Saham waqf is a permissible fund, according to Muslim jurists, to assist waqf institutions in financing the development of waqf properties and other socio-economic projects. Nevertheless, the current practice of funds has unaddressed limitations that the saham waqf fund is illiquid, resulting in inadequacy of funds for waqf properties and other socio-economic developments. This study was conducted to overcome such restrictions. The study adopted a qualitative research design to achieve the objectives. A literature review and case study approach were used. Four waqf institutions were selected as case studies. The secondary data for literature review were gathered from annual reports, official websites, related journal articles, and textbooks. Primary data were obtained from observations and face-to-face semi-structured interviews. Both primary and secondary sources were compiled and analysed by using content analysis method. The result showed that the method of saham waqf had some restrictions that could not assist waqf institutions from having continuous liquid funds. For that reason, the fund should be restructured. Therefore, this study was proposed a new conceptual framework for saham waqf by including elements of Sharia-compliant investment to assist waqf institutions in having adequate liquid funds and provide continuous socio-economic projects for the ummah.